ANALISIS HUBUNGAN DUKUNGAN KELUARGA (INTERPERSONAL) DAN PERILAKU BERISIKO DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI DESA MAYANGREJO, KECAMATAN KALITIDU, KABUPATEN BOJONEGORO - Imam Syafi'i (Kesmas Indonesia, 2023)
Dengue Hemorrhagic Fever (DHF) is an endemic disease whose incidence continues to increase every year. Factors that influence the occurrence of Dengue Hemorrhagic Fever (DHF) include environmental factors, age, knowledge, attitudes, and behavior. This study aims to determine the relationship between family support (interpersonal) and risky behavior with the incidence of Dengue Hemorrhagic Fever (DHF) in Mayangrejo Village, Kalitidu District, Bojonegoro Regency. An analytic study with a cross sectional design with a population of 3.024 people. Sampling was carried out using the Lemeshow method and obtained a sample of 67 respondents. Collecting data using a questionnaire distributed to residents' homes and data analysis using the Chi-Square Test. Of the 67 respondents, the majority are residents with an elementary education category of 56.72%, ages 21-40 and 41-60 years respectively 44.78%, location of residence in Gempol 43.28%, female 62.69%, not working 61.19%, family support (interpersonal) high 79.10%, good risk behavior 76.12%. The results of the Chi-Square Test analysis between family support (interpersonal) with the incidence of Dengue Hemorrhagic Fever (DHF) in Mayangrejo Village, Kalitidu District, Bojonegoro Regency showed p-value = 0.12, which means that there is no relationship between the two because the p-value> 0 ,05. Meanwhile, between risk behavior and the incidence of Dengue Hemorrhagic Fever (DHF) in Mayangrejo Village, Kalitidu District, Bojonegoro Regency shows a p-value = 0.022, which means that there is a relationship between the two because the p-value <0.05. Keywords: Dengue Hemorrhagic Fever (DHF), Family support (interpersonal), Risky behavior.